A case of acute lymphoblastic leukaemia disease with pancreatic mass as the first symptom confirmed by elastography combined with EUS-FNA. Issue 10 (October 2022) - Jia, Xing-Fang; Chen, Liang; Wang, Nana; Liu, Xiao; Yan, Hui; Zhang, Fan; Gong, Jing; Liu, Cheng-Xia; Shi, Ning
Haematological diseases with pancreatic masses as the first symptom are clinically rare but should not be ignored. This case report describes a 60-year-old female patient with acute leukaemia that had a pancreatic mass as her first symptom. The patient was admitted and elastography combined with endoscopic ultrasound (EUS) guided fine needle aspiration biopsy (EUS-FNA) was used for diagnosis, treatment planning and determination of prognosis. The site selected for the EUS-FNA puncture was the caudal section of the pancreatic body and the posterior wall of the gastric body was used as the puncture point. The elastography view of the head of the pancreas was blue/green with predominant blue colour. A 19 G puncture needle with a slow-draw core and two stitches of micro-negative pressure were used. Cytology detected heterotypic cells, pancreatic puncture histopathology, the presence of pancreatic alveolar structures and heterotypic tumour cells in the interstitium. Immunohistochemistry of the pancreatic puncture tissue showed B-cell lymphoblast-derived tumours and bone marrow puncture indicated acute lymphoblastic leukaemia. The patient was diagnosed with acute lymphoblastic leukaemia invading the pancreas and was treated with chemotherapy. After treatment, her condition was stable. Follow-up is ongoing and there have been no signs of tumour recurrence or metastasis.